2019
DOI: 10.1111/imcb.12284
|View full text |Cite
|
Sign up to set email alerts
|

RIPLET, and not TRIM25, is required for endogenous RIG‐I‐dependent antiviral responses

Abstract: The innate immune system is our first line of defense against viral pathogens. Host cell pattern recognition receptors sense viral components and initiate immune signaling cascades that result in the production of an array of cytokines to combat infection. Retinoic acid–inducible gene‐I (RIG‐I) is a pattern recognition receptor that recognizes viral RNA and, when activated, results in the production of type I and III interferons (IFNs) and the upregulation of IFN‐stimulated genes. Ubiquitination of RIG‐I by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 56 publications
3
75
0
Order By: Relevance
“…Several E3 ligases other than TRIM25 promote ubiquitination of RIG-I leading to controversial discussions about their relative importance (64)(65)(66)(67)(68)(69). Among these are several TRIM proteins (TRIM4, 15,40) and Riplet, a close relative of TRIM25, that lost the B-Box domains and parts of the CC (70)(71)(72).…”
Section: Discussionmentioning
confidence: 99%
“…Several E3 ligases other than TRIM25 promote ubiquitination of RIG-I leading to controversial discussions about their relative importance (64)(65)(66)(67)(68)(69). Among these are several TRIM proteins (TRIM4, 15,40) and Riplet, a close relative of TRIM25, that lost the B-Box domains and parts of the CC (70)(71)(72).…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by ubiquitination at various sites on the 2CARD by Riplet, TRIM25, TRIM4 and MEX3C. This would fit with several recent observations (Cadena et al, ; Hayman et al, ; Shi et al, ) that Riplet is absolutely required for efficient RIG‐I signaling activation, while TRIM25 is not, as well as explaining why there is seemingly redundancy between the other E3 ligases. In particular, recent work by Cadena et al showed that deletion of TRIM25 from HEK293T and MEF cells results in an increase, not a reduction in RIG‐I activation in response to 5′ppp‐RNA.…”
Section: Trim25's Role In Innate Immunitymentioning
confidence: 99%
“…The notion of different E3 ligases playing critical roles in the activation of RIG-I has recently been challenged with some groups identifying Riplet, and not TRIM25, as the required E3 ligase [126][127][128]. The challenge was raised when Riplet -/-, but not TRIM25 -/-, cell lines failed to induce innate immune signalling upon stimulation [126], although these experiments did not address different time points or other stimulation conditions that may trigger RIG-I activation, or the possibility of functional redundancy.…”
Section: Innate Antiviral Signalling Functions Of Trim25: Rig-i-depenmentioning
confidence: 99%